Core Decompression and Biological Treatment in Osteonecrosis of the Hip due to Systemic Lupus Erythematosus, 8-year Follow-up: A Case Report - Rhatomy, Sholahuddin; Dilogo, Ismail Hadisoebroto (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Osteonecrosis most commonly affects the femoral head, especially in middle-aged adults. It can be caused by trauma, chronic inflammation, or infection. It leads to collapse of the entire femoral head and culminates with total hip replacement. CASE REPORT: A 29-year-old female with systemic lupus erythematosus (SLE) had a chief complaint of bilateral hip pain. She was diagnosed with early osteonecrosis of the femoral head (FICAT stage II) using magnetic resonance imaging and core decompression surgery was performed using three small diameter (4 mm) drillings and added biological treatment. She was evaluated with a visual analog scale (VAS), Harris hip score (HHS), and plain radiography in the pre-operative stage and post-operative follow-up. RESULTS: Functional outcome at 8-year follow-up showed improvement with significantly decreased VAS (pre-operative: 5, post-operative: 0), significant improvement of HHS from 52.725 points (poor) pre-operative to 92.025 points (excellent) post-operative, and subsided femoral head lesion. CONCLUSIONS: Surgical decompression and biological treatment result in decreased intraosseous pressure and enhanced osteogenesis. It can restrict the SLE disease progression and limit the number of cell death.